AI-Supported Translation Learning in EFL Contexts: Insights from Students - Sri Widyarti Ali (Jurnal Wacana Sosial Nusantara, 2025)
The rapid integration of artificial intelligence (AI) has transformed language education, including translation learning in English as a Foreign Language (EFL) contexts. In translation classrooms, AI-based tools such as machine translation engines, large language models, and AI-assisted revision systems are increasingly used to support comprehension, problem-solving, and decision-making. However, empirical studies that foreground students’ perspectives on AI-supported translation learning remain limited, particularly in EFL higher education. This study explores EFL students’ experiences, perceptions, and learning practices related to the use of AI in translation learning. Adopting a qualitative research design, data were collected through semi-structured interviews with undergraduate students enrolled in a translation course in an English Education program. The data were analyzed using thematic analysis to identify recurring patterns across participants’ accounts. The findings reveal seven major themes, including AI as a cognitive support tool, a scaffold for linguistic and cultural awareness, a trigger for metacognitive reflection, and a source of ethical consideration. Overall, the study shows that students perceive AI not as a shortcut, but as a learning companion that reshapes their translation strategies and awareness. These findings contribute to a deeper understanding of AI-mediated translation learning and offer pedagogical insights for the meaningful integration of AI in EFL translation education.